2022
DOI: 10.3390/membranes12020213
|View full text |Cite
|
Sign up to set email alerts
|

Chia Seed Mucilage Edible Films with Origanum vulgare and Satureja montana Essential Oils: Characterization and Antifungal Properties

Abstract: Films made with mucilage obtained from defatted chia seeds and incorporated with oregano (Origanum vulgare) and savory (Satureja montana) essential oils (0.1,1.0 and 1.5% v/v) were prepared to evaluate their physical, optical, mechanical and antifungal properties as well as their microstructure. The use of different types of essential oils (oregano or savory) only had a significant effect on the light transmittance, total color difference (∆E) and antifungal activity of the films. However, the kind of essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…On the contrary, the film containing BCS oil (F3) exhibited a cracked structure and pores, possibly due to the evaporation of the essential oil from BCS oil during drying. This was also evident from a study by Muñoz-Tébar et al [37], who reported that films comprised of chia mucilage and essential oil exhibited smooth surfaces devoid of pores or cracks, indicating that the film solution maintained a stable emulsion system after drying. The same results were also observed by Ghamari et al [15], who found a pore and crack structure in the film's microstructure containing BCS oil.…”
Section: Surface Morphology Of the Biocomposite Film Using Semsupporting
confidence: 57%
“…On the contrary, the film containing BCS oil (F3) exhibited a cracked structure and pores, possibly due to the evaporation of the essential oil from BCS oil during drying. This was also evident from a study by Muñoz-Tébar et al [37], who reported that films comprised of chia mucilage and essential oil exhibited smooth surfaces devoid of pores or cracks, indicating that the film solution maintained a stable emulsion system after drying. The same results were also observed by Ghamari et al [15], who found a pore and crack structure in the film's microstructure containing BCS oil.…”
Section: Surface Morphology Of the Biocomposite Film Using Semsupporting
confidence: 57%
“…The results showed that, the smaller the amount of chia flour, the lower the film thickness, going from 0.274 to 0.194 mm, contrary to its moisture content, which decreased as the chia flour content was higher (from 12.23% to 7.42%); regarding solubility in water, there was no greater variation because the levels remained between 25.43% and 25.57%. Another study of films made with chia is the study carried out by Muñoz‐Tébar et al (2022) in which films were made with chia mucilage and essential oils of Origanum vulgare and Satureja montana ; in this the use of different types of essential oils only had a significant effect on the light transmission, the total color difference (∆ E ) and the antifungal activity of the films. However, the type of essential oil was not significant for the physical, optical and mechanical properties of the films.…”
Section: Iberoamerican Crops As a Resource For Obtaining Biofilms: Ch...mentioning
confidence: 99%
“…Four other research groups studied the performance of antimicrobial compounds when incorporated into a film matrix. Muñoz-Tébar et al [3] prepared bioplastics with chia mucilage, which also contained Origanum vulgare and Satureja montana essential oils, and tested their antifungal, mechanical and physical properties. In addition, Santos et al [4] prepared PLA-based films with bactericidal activity against Listeria mono-cytogenes and Salmonella enterica by adding MXene (Ti 3 C 2 T x ) into the film composition.…”
mentioning
confidence: 99%